"Вершник без голови": скіфське поховання в кургані біля Кусторівки - Козак, О.Д.; Окатенко, В.M.; Бітковська, Т.B. (Археологія і давня історія України, 2021)
Залучаються до наукового обігу археологічні,
антропологічні та археозоологічні матеріали з
впускного чоловічого поховання раннього залізного
віку; аналізується незвичайний поховальний обряд
та зміни на скелеті людини, пов’язані з військовою спеціалізацією. In 2013 near Kustorivka village of Krasnokutsky district,
Kharkov region the Scythian burial mound (5th—4th centuries
BC.) was excavated. The inserted burial of a beheaded man
has been discovered there. Fragments of horse bones, horse
harness, numerous arrowheads, the spearhead and knife were
unearthed in the grave. Funeral inventory dates the burial to
the 2nd half or the end of 5th — the early 4th century BC.
The grave goods allowed us to suggest that the man was a
horseman and possessed a bow with arrows, javelin or lance.
These assumptions have been confirmed by anthropological
studies of the development of muscles relief, injuries and
specific skeletal markers. The skeleton showed clear signs of
a horseman’ and archer’ osteological complexes.
The man died at the age of 20—25. The skull, first and second
cervical vertebrae were absent in the undisturbed burial.
The upper part of the left intervertebral condyle of the 3rd vertebra
was cut off by the hit from left behind and below. These
signs are evidence of decapitation. In addition, numerous cut
marks made with a sharp blade were found on the anterior
and lateral surfaces of the 3rd and 4th cervical vertebrae, as
well as on the left femur above the knee. Thus could be the
signs of the body cleaning of waste tissue for its transportation
or in course of the preparation for the burial.
Studies of the horse’s remains showed that it has deceased
at the age of 10—12 years. The horse was decapitated
as well by the hit directed between first and second cervical
vertebra. The head was also cut in half and only one part
of it was present in the burial. There were also some bones
of the animal’s skeleton, which do not belong to the edible
parts of the body. The severed head of the horse was located
above the place where the man’s head was supposed to be,
thus the horse harness was situated on the level of the human
skeleton.
Traces of the possible preparation of the human body for
burial and the location of the remains of a horse over a lost
human head along with other changes in the skeleton indicate
a certain funeral rite, direct analogies of which have not
yet been found in the North Pontic region.